Advances in insect physiology : volume 39 - Simpson, Stephen J. (Elsevier/Academic Press, 2010)
Includes reviews on various aspects of insect physiology. This title is suitable for invertebrate physiologists and neurobiologists, entomologists, zoologists and insect biochemists